Biomechanical Evaluation of a Novel Lisfranc Injury Cadaveric Model Using Supination and Pronation Testing. Issue 4 (16th October 2019) - Wagner, Emilio; Wagner, Pablo; Baumfeld, Daniel; Baumfeld, Tiago; Prado, Marcelo; Nery, Caio
Category: Basic Sciences/Biologics, Sports, Trauma Introduction/Purpose: Lisfranc joint injuries occur due to direct or indirect trauma, where twisting forces are applied. Cadaveric models have been used to evaluate injury patterns and fixation methods, but a frequent limitation has been historically the small amount of joint displacement after injury, which hinders a correct evaluation of the damage degree and reconstruction effectiveness. Our hypothesis was that adding pronation and supination motion to a cadaveric model would produce reliable and measurable joint displacements. Methods: 24 fresh frozen lower leg cadaveric specimens were utilized. The medial (C1), intermediate (C2) cuneiforms, first (M1) and second (M2) metatarsal bones were marked. A complete ligament injury was performed between C1-C2 and C1-M2 in 12 specimens (Group 1), and between C1-C2, C1-M2, C1-M1 and C2-M2 in 12 matched specimens (Group 2). Supination and pronation motion of the forefoot relative to the hindfoot was obtained through internal and external rotation of the tíbia, using an Instrom machine. A 3D Digitizer was used to measure distances between the bones already mentioned. Results: Distance C1-C2 increased 3 mm after ligament injury with supination motion (p<0.05). Distance C1-M2 increased 4 mm after ligament injury with pronation motion (p<0.05). Distances between C1-M1 and C2-M2 only changed in Group 2, increasing 3 mm and 2 mm respectively (p<0.05). Conclusion: Pronation and supination motion of the forefoot relative to the hindfoot produces measurable joint displacements in a cadaveric Lisfranc injury model. We believe this new method for testing cadaveric lisfranc injuries will allow a better understanding of injury patterns and repair or reconstruction techniques.